082 Obstructive sleep apnoea in idiopathic intracranial hypertension: a sub-study of the IIH-WT randomised controlled trial. Issue 9 (12th August 2022) - Yiangou, Andreas; Mitchell, James; Nicholls, Matthew; Chong, Yu Jeat; Vijay, Vivek; ley, Benjamin Waker-; Lavery, Gareth; Tahrani, Abd A; Mollan, Susan P; Sinclair, Alexandra J
Abstract : Obesity is a risk factor for idiopathic intracranial hypertension (IIH) and obstructive sleep apnoea (OSA). We aimed to determine the prevalence of OSA in IIH and evaluate the diagnostic performance of OSA screening tools in IIH. Additionally, we evaluated the relationship between weight loss, OSA and IIH over 12-months. A sub-study of a multi-centre, randomised controlled parallel group trial comparing the impact of bariatric surgery vs. community weight management intervention (CWI) on IIH (IIH:WT). OSA was assessed using home-based polygraphy at baseline and 12-months. Of the 66 women in the IIH:WT trial, 46 were included in this sub-study. OSA prevalence was 47% (n=19). The STOP-BANG had the highest sensitivity (84%) compared to the Epworth Sleepiness Scale (69%) and Berlin (68%) to detect OSA. Bariatric surgery resulted in greater reductions in AHI vs. CWI (-2.8 [-11.9, 0.7], p=0.017). Over 12 months there was a positive association between changes in papilloedema and AHI (r=0.543, p=0.045), despite adjustment for changes in body mass index (R2=0.522, p=0.017). OSA is common in IIH and the STOP-BANG questionnaire was the most sensitive screening tool. Bariatric surgery improved OSA in patients with IIH. The improvement in AHI was associated with improvement in papilloedema independent of weight loss.